2019
DOI: 10.1186/s12866-019-1624-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antimicrobial susceptibility and plasmid profiling of Vibrio spp. isolated from cultured groupers in Peninsular Malaysia

Abstract: BackgroundNumerous prevalence studies of Vibrio spp. infection in fish have been extensively reported worldwide, including Malaysia. Unfortunately, information on the prevalence of Vibrio spp. in groupers (Epinephelus spp.) is limited. In this study, groupers obtained from nine farms located at different geographical regions in Malaysia were sampled for the presence of pathogenic Vibrio spp. and their susceptibility profiles against seven antibiotics.ResultsOut of 270 grouper samples, 195 (72%) were detected w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 55 publications
8
21
2
Order By: Relevance
“…The results obtained in the present work are consistent with the results obtained in studies carried out by other authors (Elhadi et al, 2004;Jacobs et al, 2017;Vu et al, 2018;Amalina et al, 2019;Sadat et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results obtained in the present work are consistent with the results obtained in studies carried out by other authors (Elhadi et al, 2004;Jacobs et al, 2017;Vu et al, 2018;Amalina et al, 2019;Sadat et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrates the prevalence of Vibrio spp., in groupers and the distribution of multidrug resistance strains that could be of concern to the farmers in Malaysia. In addition, data from this study can be further used in fish disease management plan (Amalina et al, 2019).…”
Section: Antecedentsmentioning
confidence: 98%
“…The findings were also in agreement with studies of Parvathi et al (2011) which presented various antibiotic especially penicillin and bacitracin. In contrast to previous studies, it is reported that Vibrio isolates (56%) were susceptible against bacitracin (Parvathi et al, 2011;Amalina et al, 2019).…”
Section: Susceptibility Of Antibiotics Testingmentioning
confidence: 60%
“…Huang et al, 2018). Methyl-accepting chemotaxis protein (MCP) (K03406) was present in Asian seabass, and was associated with the genus Vibrio, which is known for its pathogenicity and disease outbreaks (Amalina et al, 2019;Mohamad et al, 2019aMohamad et al, , 2019b. MCP is a sensory transducer that controls exopolysaccharides (EPS) production (Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%